A NEW CMOS DESIGN AND ANALYSIS OF CURRENT CONVEYOR SECOND GENERATION (CCII) - شخطور Mahmoud; عكاشة Alaa (مجلة العلوم الإنسانية والتطبيقية, 2016)
This paper describes the current conveyors used as a basic building block in a variety of electronic circuits in instrumentation and communication systems. Today these systems are replacing the conventional Op-amp in many applications such as active filters, and analog signal processing. Current conveyors are unity gain active building blocks having high linearity, wide dynamic range, and provide higher gain bandwidth The proposed current conveyors are simulated using TSMC 0.18um CMOS technology on Advanced Design System and the results are also tabulated for comparison. The main features of these current conveyors are low voltage, less power, high slew rate, and wide bandwidth for voltage transfer (Vy to Vx) and current transfer (Ix to Iz) which make them suitable for high-frequency and low-power applications.